Health seeking behavior of the mothers for the special care new-born unit discharged children: A comparative study - Gursimer Jeet; Atul Sharma; Tulika Goswami Mohanta; Ajay Trakroo (Wolters Kluwer Medknow Publications, 2013)
Establishment of special care new-born units (SCNU) in hospitals not only serves to provide the intensive care to sick neonates, but presents with opportunities to enhance knowledge and modify attitude and practices of their parents through behavior change communication (BCC). A cross-sectional study was conducted in Dibrugarh District, Assam from January to June, 2011 to assess differences in health-care seeking behavior of these mothers from mothers of newborns who were born at home and mothers who had normal uneventful institutional deliveries. Mothers of 29 SCNU discharged, 34 institutions delivered and 26 home delivered children were interviewed using a semi-structured interview schedule and a knowledge, attitude and practice (KAP) survey tool. Mothers of children admitted to SCNU scored better in questions related to vaccination, contraception, protection of child from infections and cold and perceptions about traditional healers, but overall KAP scores in the three groups were not found significantly different.